2012
DOI: 10.1063/1.3703470
|View full text |Cite
|
Sign up to set email alerts
|

Chromium-oxide enhancement of photo-oxidation of CdSe/ZnS quantum dot solids

Abstract: Published by the American Institute of Physics. Related ArticlesEffect of dimensionality and morphology on polarized photoluminescence in quantum dot-chain structures J. Appl. Phys. 112, 084314 (2012) Quasiresonant excitation of InP/InGaP quantum dots using second harmonic generated in a photonic crystal cavity Appl. Phys. Lett. 101, 161116 (2012) Size-dependent radiative decay processes in graphene quantum dots Appl. Phys. Lett. 101, 163103 (2012) Optical absorbance of doped Si quantum dots calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 47 publications
(70 reference statements)
0
18
0
Order By: Relevance
“…12,13 Recently, we have shown that nano-scale-thin layers of metal oxides can have significant impact on the photo-induced properties of colloidal QDs. 14,15 Our results demonstrated that, depending on the types of these oxides and the basesubstrates on which they were deposited, such oxides could promote unique sets of photo-induced processes in such QDs.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…12,13 Recently, we have shown that nano-scale-thin layers of metal oxides can have significant impact on the photo-induced properties of colloidal QDs. 14,15 Our results demonstrated that, depending on the types of these oxides and the basesubstrates on which they were deposited, such oxides could promote unique sets of photo-induced processes in such QDs.…”
Section: Introductionmentioning
confidence: 74%
“…14 On the other hand, when 1 nm of Cr oxide is deposited on a borosilicate glass base-substrate, it can profoundly accelerate the rate of photo-oxidation of the QDs. 15 We have also shown that when metallic nanoparticles are coated with an ultrathin layer of Cr oxide, the plasmonic enhancement of the energy transfer between CdSe/ZnS QDs can be suppressed with irradiation. 16 These prior results suggest that when a substrate is coated with an ultrathin layer of a specific metal oxide, it can be used as a photo-active substrate to study some of the characteristic features of QDs using the unique photocatalytic effects of the oxide.…”
Section: Introductionmentioning
confidence: 76%
“…[ 31 ] This can change the exciton transition energies and increase of their nonradiative decay rates. [ 6,7,32 ] Figure shows the evolution of the emission spectra of the PbS QDs on a glass substrate covered with Si after they were irradiated with the 514 nm laser for a given period of time (legends in seconds). The laser power was 2 mW power, and the maximum irradiation time was 300 s. The results show blueshift of the emission spectra as the irradiation time was increased.…”
Section: Methodsmentioning
confidence: 99%
“…These are indications of oxidation and formation of defect sites. [ 31,32 ] Considering these issues, the measurements presented in this paper were taken within a few seconds of exposure to the laser beam and immediately after preparation of samples. As for the case of TCSPC, we reduced the average laser intensity to less than 0.03 mW.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the Cr oxide can induce strong photooxidation of QDs and suppression of PFE. 13 When MNPs are coated with a ultrathin layer of Cr oxide and irradiated, this accelerated photo-oxidation can even supress plasmonic enhancement of F€ orster resonance energy transfer (FRET) between QDs. 14 In this paper, we investigated the emission of QDs when they were deposited on plasmon-metal oxide substrates.…”
mentioning
confidence: 99%